RETORIKA SEBAGAI ILMU KOMUNIKASI DALAM PENDIDIKAN - Umi Faizah (p-ISSN 2356-0576, 2014)
ABSTRACT: Rhetoric is the science that provides a way related or human interaction with another human being through communication. Rhetoric can be used in education. Complementary set of tools or used by teachers or educators in order to communicate with students or learners, among others, using 1 ) auditif media , is media which can only be heard alone, or media only have sound elements, such as radios, tape recorders, cassette, LPs and sound recordings. 2 ) visual media, is media which can only be seen alone, it does not contain other elements of sound between slide film, photographs, transparencies, paintings, drawings, and various forms of printed material such as graphics and other media. 3 ) audio- visual media, is media types other than an element of sound is also an element of the image that can be seen, such as video recordin, various sizes films, slides voice. Benefits of communications media in education broadly that add excitement and student motivation. Utilization of communication media in education continues to grow in accordance with the development of the concept of learning and should be based on the principles of appropriate and aimed at the achievement of educational goals. Media used were directed facilitate student learning in an effort to understand the subject matter, should match the learning objectives, learning materials, interests, needs and conditions of the students, watching effectiveness , and in accordance with the teacher's ability to operate it. Key words: Rhetoric, communication, education ABSTRAK: Retorika merupakan ilmu yang menyajikan cara berhubungan atau interaksi  manusia dengan manusia lain melalui komunikasi. Retorika dapat dipakai dalam bidang pendidikan. Seperangkat alat bantu atau pelengkap yang digunakan oleh guru atau pendidik dalam rangka berkomunikasi dengan siswa atau peserta didik antara lain mengunakan 1) media uditif, yaitu media yang hanya dapat didengar saja, atau media yang hanya memiliki unsur suara, seperti radio, tape recorder, kaset, piringan hitam dan rekaman suara.  2) Media visual, yaitu media yang hanya dapat dilihat saja, tidak mengandung unsur suara antara lain film slide, foto, transparansi, lukisan, gambar, dan berbagai bentuk bahan yang dicetak seperti media grafis dan lain sebagainya. 3) Media audio visual, yaitu jenis media yang selain mengandung unsur suara juga mengandung unsur gambar yang dapat dilihat, seperti rekaman video, berbagai ukuran film, slide suara. Manfaat media komunikasi dalam pendidikan secara garis besar yaitu menambah gairah serta motivasi belajar siswa. Pemanfaatan media komunikasi dalam pendidikan terus berkembang sesuai dengan perkembangan konsep belajar mengajar dan harus berdasarkan prinsip-prinsip yang sesuai dan ditujukan tercapainya tujuan pendidikan. Media yang digunakan diarahkan mempermudah siswa belajar dalam upaya memahami materi pelajaran, harus sesuai tujuan pembelajaran, materi pembelajaran, minat, kebutuhan dan kondisi siswa, memerhatikan keefektifan, serta  sesuai dengan kemampuan guru dalam mengoperasikannya. Kata kunci: retorika, komunikasi, pendidikkan